Studi Kelompok Siamang (Hylobates Syndactylus) Di Repong Damar Pahmungan Pesisir Barat - Erna Maya Sari; Sugeng Prayitno Harianto (Jurnal Sylva Lestari, 2015)
Repong Damar in Pahmungan, West Coastal District is a buffer of Bukit Barisan Selatan National Park (TNBBS). Repong Damar is one example of the success of agroforestry systems managed by local community that is still very traditional. This area was identified as a component of siamang (Hylobates syndactylus) habitat. The absence of data and the latest information about the siamang groups in Pekon Pahmungan were reasons of this research. The purpose of this research was to determine the siamang groups in Repong Damar, used concentrated area methode. The research was done on April 2015. The results showed that the existence of siamang group in Repong Damar Pahmungan were 4 individuals/group. The distribution of age classes in the individual phases of adult siamang were 2 individuals and the individual of adolescent phase were 2 individuals. The sex ratio in the adult age class phase was 1:1 and at adolescent age class phase was 1:1. Keywords: siamang, groups, repong damar